2021
DOI: 10.3168/jds.2021-20211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of olive leaves feeding on phenolic composition and lipolytic volatile profile in goat milk

Abstract: The aim of this study was to evaluate phenolic composition, antioxidant potential, and lipolytic events in raw milk obtained from goat fed a dietary supplementation with olive leaves (OL), a by-product of the olive oil production chain. For this purpose, 30 Saanen goats were randomly allocated into 2 groups of 15 goats each: the control group received a standard diet that was prepared by taking into account the nutritional needs of lactating goats, whereas the experimental group (EG) was fed with an OL-supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Animal models included were sheep (2 papers), cows (9 papers) and goats (4 papers). Some studies also reported the progeny of the animals such as primiparous (Safari et al ., 2018; Li et al ., 2021) and multiparous (Hausmann et al ., 2018; Safari et al ., 2018; Li et al ., 2021; Wang et al ., 2021) and included the period of lactation (Ianni et al ., 2019, 2021; Bonanno et al ., 2019b; Mapato et al ., 2021; Menci et al ., 2021) or specified mid-lactation (Scuderi et al ., 2019; Simitzis et al ., 2019). Design of the studies included randomized (Cais-Sokolińska et al ., 2015; Hausmann et al ., 2018; Safari et al ., 2018; Ianni et al ., 2019; Bonanno et al ., 2019a; Walkenhorst et al ., 2020; Li et al ., 2021; Wang et al ., 2021), stratified (Scuderi et al ., 2019; Walkenhorst et al ., 2020), allocated (Delgadillo-Puga et al ., 2019; Simitzis et al ., 2019) and 4 × 4 Latin square design with a 2 × 2 factorial arrangement (Mapato et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Animal models included were sheep (2 papers), cows (9 papers) and goats (4 papers). Some studies also reported the progeny of the animals such as primiparous (Safari et al ., 2018; Li et al ., 2021) and multiparous (Hausmann et al ., 2018; Safari et al ., 2018; Li et al ., 2021; Wang et al ., 2021) and included the period of lactation (Ianni et al ., 2019, 2021; Bonanno et al ., 2019b; Mapato et al ., 2021; Menci et al ., 2021) or specified mid-lactation (Scuderi et al ., 2019; Simitzis et al ., 2019). Design of the studies included randomized (Cais-Sokolińska et al ., 2015; Hausmann et al ., 2018; Safari et al ., 2018; Ianni et al ., 2019; Bonanno et al ., 2019a; Walkenhorst et al ., 2020; Li et al ., 2021; Wang et al ., 2021), stratified (Scuderi et al ., 2019; Walkenhorst et al ., 2020), allocated (Delgadillo-Puga et al ., 2019; Simitzis et al ., 2019) and 4 × 4 Latin square design with a 2 × 2 factorial arrangement (Mapato et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Interventions with plants, herbs, seeds, grains and isolated bioactive compounds were used in the studies. Among the plants included in the interventions were Acacia farnesiana (Delgadillo-Puga et al ., 2019), bamboo grass (Mapato et al ., 2021), olive leaves (Ianni et al ., 2021), herbal feed additives (Walkenhorst et al ., 2020) and Perilla frutescens leaf (Wang et al ., 2021). Other studies included seeds such as false flax cake (Cais-Sokolińska et al ., 2015) and pomegranate seeds (Safari et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen mL of each milk sample were cool centrifugated at 4000× g rpm for 15 min. The fat was removed, the supernatant was recovered, filtered and quantified using Bradford method [24] and Bovine Serum Albumine (BSA) as standard. Protein samples (7.5 µg) were diluted in sample buffer (0.5 M Tris-HCl, pH 6.8; 2% (w/v) SDS; 7% (v/v) glycerol; 4.3% (v/v) β-mercaptoethanol; 0.0025% (w/v) bromophenol blue), boiled for 5 min and loaded into a 12% polyacrylamide gel.…”
Section: Milk Protein Extraction and Sds-pagementioning
confidence: 99%